Research and Progress of Immunotherapy for Gastric Cancer in the Perioperative Period - Ammar Mubassam; Liu Hai Yan; Sohaib Mubassam; Zeeshan Rafaqat; Abdullah Zahid; Nouman Akram (Yayasan Mata Pena Madani, 2025)
This study aims to review and synthesize current evidence on the efficacy, safety, and biomarker-driven strategies of immunotherapy in the perioperative management of gastric cancer. A narrative literature review and meta-analysis were conducted by analyzing 24 relevant studies, including randomized clinical trials, phase I/II trials, systematic reviews, and cohort studies. Data were extracted from multiple databases focusing on neoadjuvant and adjuvant use of ICIs such as nivolumab and pembrolizumab. Neoadjuvant immunotherapy demonstrated favorable tumor downstaging and pathological response rates, particularly in microsatellite instability-high (MSI-H) and PD-L1 positive tumors, with manageable safety profiles. The CheckMate-577 trial highlighted the benefit of adjuvant nivolumab in prolonging disease-free survival in resected esophageal and gastroesophageal junction cancers, with ongoing trials expected to clarify effects in gastric cancer. Meta-analysis revealed improved disease-free survival (HR 0.70) and overall survival (HR 0.75) with perioperative ICIs, alongside a mild increase in immune-related adverse events. Biomarker-driven selection remains crucial for optimizing therapeutic benefit. Perioperative immunotherapy shows promise as a safe and effective approach for improving outcomes in resectable gastric cancer, particularly when guided by molecular biomarkers. Further large-scale phase III trials are needed to establish new standards of care.